2007
DOI: 10.1097/01.rli.0000258059.82552.55
|View full text |Cite
|
Sign up to set email alerts
|

Improved Evaluation of Myocardial Perfusion and Viability With the Magnetic Resonance Blood Pool Contrast Agent P792 in a Nonreperfused Porcine Infarction Model

Abstract: Unlike Gd-DOTA, the blood pool contrast agent P792 allows evaluation of myocardial perfusion for a period of 30 minutes and shows good agreement with histomorphometry. P792 must be examined in further studies to evaluate its potential in evaluating early myocardial lesions and reperfusion. In addition, P792 also allows for evaluation of myocardial viability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…administration of higher effective doses, such as MRI contrast agents. It has been previously reported that negatively charged macrocyclic contrast agents are well tolerated by the cardiovascular system 51,52. Our experiments with anionic DOTA-tetraamide complexes indicate that one way in which the problem of complex toxicity can be overcome is by the use of negatively charged ligand systems such as 2 or 4 .…”
Section: Discussionmentioning
confidence: 51%
“…administration of higher effective doses, such as MRI contrast agents. It has been previously reported that negatively charged macrocyclic contrast agents are well tolerated by the cardiovascular system 51,52. Our experiments with anionic DOTA-tetraamide complexes indicate that one way in which the problem of complex toxicity can be overcome is by the use of negatively charged ligand systems such as 2 or 4 .…”
Section: Discussionmentioning
confidence: 51%
“…Several studies showed that perfusion defects and viability in acute myocardial infarction can be reliably assessed after administration of intravascular contrast agents. [27][28][29] However, in the setting of chronic myocardial infarction most of the studies with contrastenhanced MRI were performed with extracellular contrast agents, and most among those with gadopentetate dimeglumine. Extracellular contrast materials with the potential to decrease T1 values to a greater extent compared with Gd-DTPA offer the possibility to improve the delineation of infarcted myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Recent technical advances in myocardial perfusion imaging with magnetic resonance imaging (MRI), such as the use of parallel imaging 4 and intravascular contrast agents, 5 and the development of novel approaches with blood oxygen-level dependent contrast 5 seem bound to turn MRI into an increasingly useful tool for the diagnoses of coronary artery disease. There is compelling evidence that any impairment of the coronary hyperemic response does not simply reflect the presence and severity of any up-stream coronary lesions, but is a sensitive marker of coronary vasoreactivity.…”
mentioning
confidence: 99%